Kesesuaian Penggunaan Obat Antihipertensi pada Pasien Hipertensi di Puskesmas Krobokan Semarang - Rochayati Rochayati; Maria Caecilia Nanny Setiawati (BORNEO JOURNAL OF PHARMASCIENTECH, 2021)
Hypertension is a persistent increase in blood pressure. Hypertensive patients receive antihypertensive therapy to lower their blood pressure. Many references are used when providing therapy in hypertensive patients. The purpose of this study was to determine the suitability of the use of antihypertensive drugs in hypertensive patients at the Krobokan Public Health Center Semarang according to JNC VIII. This research is an observational descriptive study with retrospective data collection. Data were taken from medical records of hypertensive patients aged more than 26 years who received antihypertensive therapy for the period November-December 2019 for two consecutive months. The data obtained were analyzed qualitatively including patient characteristics and calculated the suitability of the use of antihypertensive drugs to blood pressure according to JNC VIII Medical Records of hypertensive patients according to inclusion in the period November-December 2019 as many as 87 patients with the results Characteristics of patients receiving antihypertensive drugs are as follows : The number of female patients is 75.87% and the most age range is 56-65 years at 34.49%, the longest suffering from hypertension is 1-3 years at 64.37%. Patients underwent examination 243 times during the study period. The appropriate use of antihypertensive drugs according to the JNC VIII literature in November was 71 cases (58.68%) while in December there were 107 cases (87.70%)